HYPER-PARABOLOIDA DALAM RUANG EUCLID BERDIMENSI-N - Rahmat, Muhammad Syifaur; Suhito, Suhito; Sutarto, Hery (Universitas Negeri Semarang, 2016)
One study in geometry is parabolic and paraboloid. Parabola is the locus of points equidistant from a given point and line. Expansion paraboloida on space n> 3 can be done by working through its analytical properties. Issues raised is how to find and formulate general equation of hyper-paraboloid, hyper-paraboloid tangent plane, and the polar plane of hyper-paraboloid. The purpose of this research is to formulate a general equation-paraboloida hyper, hyper-paraboloida tangent plane, and the polar plane of hyper-paraboloid. The method used is literature. In this study, the authors limit the issues discussed in the hyper-paraboloid centered at O and O’ with a symmetry axis parallel to the coordinate axes as well as the focal point lies on the axis symmetry. Results of this research is the general equation of hyper-paraboloid, hyper- paraboloid tangent plane, and the polar plane of hyper-paraboloid